Good omens : the nice and accurate prophecies of Agness Nutter, witch - Pratchett, Terry; Pratchett, Terry (New York : William Morrow, 2006)
When Agnes Nutter predicts that the end of the world is days away, the demon Crowley and his angel friend, Aziraphale, team up to save humankind.
Booklist
Library Journal Starred
Wilson's Fiction
Booklist, June 2006
Library Journal Starred, March 1999
Voice of Youth Advocates (V.O.Y.A.), February 2007
Keywords: End of the world -- Fiction; Witches -- Fiction; Fantasy fiction; Humorous fiction; Witches -- Fiction; Fantasy fiction; Humorous fiction